Analisa Aerodinamika Bodi Kendaraan Mataram Proto Diesel dengan ANSYS 15.0 - I Gusti Gde Badrawada; Adi Purwanto; Edo Riyan Firlanda (Proklamasi 45 University, 2019)
The goal of this research was to find out the aerodynamic body design of Mataram Proto. Using Solidwork 2015 for modeling the body and Ansys 2015 for numerical simulation were the main tools of this research. The body was drawn with scale 1: 1 and then imported into Ansys 2015 for meshing. The unstructured meshes were used in this research. After those, using Ansys 2015, the numerical simulation was conducted with viscous model k - e with realizable type. The result of this research was the average drag coefficient of the original Mataram Proto body was 0,17 and its average lift coefficient was 0.17. For the modification Mataram Proto body, the average drag coefficient was 0.06 and 0.13 for average lift coefficient. These proved that the modification Mataran Proto body was more aerodynamic.